An analysis of people’s perceptions on Chinatown in Windhoek. - Johanna E., Iipinge (Namibian Journal for Research, Science and Technology, 2022)
This study set out to find the people’s perceptions about Chinatown in Windhoek, Namibia. This was prompted by the negative publicity in the local media about Chinese businesses and their negative impact on local businesses in the various sectors of the economy. Chinatown in Windhoek represents an embodiment of Chinese businesses because of the large concentration in one area. Was the negative publicity in the local media, affecting peoples` perception of Chinatown? Answers to this were sought from local traders who sell more or less the same products as the Chinese in Chinatown and from Chinatown customers. Most of the local traders and Customers appreciated the existence of Chinatown for different reasons. Local traders buy things from Chinatown to resell to their customers at a profit. The customers indicated that the Chinese products are affordable. However, on the other hand, a few traders were against Chinatown because it increases competition. Some customers complained about the quality of goods but this did not deter them from shopping in Chinatown as Chinese products continued to grow since and Chinese entrepreneurs are encountered everywhere in the country, including remote villages and towns. Henceforth, this study gauged at how the local shop owners and customers perceived whether they support and approve the existence of Chinese retail enclaves in Windhoek and elsewhere across the country.